The developing mind : toward a neurobiology of interpersonal experience - Siegel, Daniel J. (Guilford, 1999)
Presents an integrative framework for understanding the interface of the brain and the social environment through childhood, adolescence, and adulthood. The author addresses fundamental questions about mental health and dysfunction as he explores the ways that interpersonal relationships influence the genetically programmed unfolding of the human mind. The volume synthesizes current knowledge from independent, usually isolated areas of research, including attachment, memory, emotion, neuroscience, genetics, and psychopathology. The chapters focus on how specific mental processes and cognitive abilities are fueled by emotional relationships throughout life. When attachment to caregivers is hindered or disrupted specific problems with memory, self-organization, and emotional regulation may result. Implications for adult states of mind, emotional competence, and relationship skills are considered, as well as links to such clinical problems as dissociation and depression. The book is intended to serve as a text for courses in psychiatry, clinical and developmental psychology, neuropsychology, and cognitive science.